2013
DOI: 10.1155/2013/813450
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogenα-Zearalanol Attenuates Homocysteine-Induced Apoptosis in Human Umbilical Vein Endothelial Cells

Abstract: Hyperhomocysteinemia is an independent risk factor for cardiovascular diseases. The enhanced nitrative stress plays an important role in homocysteine-induced endothelial dysfunction. Previous studies have showed that phytoestrogen α-zearalanol alleviated endothelial injury in ovariectomized hyperhomocysteinemic rats; however, the underlying mechanism remains to be clarified. This study was to investigate the effects of α-zearalanol on homocysteine-induced endothelial apoptosis in vitro and explore the possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…The formation of 3-NT was usually used for monitoring the generation of ONOO − in vivo. 19 Both immunohistochemistry and Western blot results indicated that the enhanced 3-NT expression in ZDF rats could be attenuated by sitagliptin treatment (Figure 3E, F). All these results implied that inhibition of nitro-oxidative stress might play a role in the protective effect of sitagliptin.…”
Section: Resultsmentioning
confidence: 84%
“…The formation of 3-NT was usually used for monitoring the generation of ONOO − in vivo. 19 Both immunohistochemistry and Western blot results indicated that the enhanced 3-NT expression in ZDF rats could be attenuated by sitagliptin treatment (Figure 3E, F). All these results implied that inhibition of nitro-oxidative stress might play a role in the protective effect of sitagliptin.…”
Section: Resultsmentioning
confidence: 84%
“…So, the expression of caspase-3 was used to evaluate Hcy-induced apoptosis in HCAECs in this study. Previous studies have found that 500 µmol/L–1 mmol/L Hcy can significantly increase the apoptosis in HUVECs [ 7 , 8 ]. In our study, the expression of caspase-3 mRNA was significantly upregulated by 1 mmol/L Hcy, and the results were consistent with the previous date.…”
Section: Discussionmentioning
confidence: 99%
“…There is a close relationship between dysfunction of endothelial cells and cardiovascular diseases [ 5 ]. Hcy can induce apoptosis in endothelial cells [ 6 , 7 , 8 ], and the apoptosis induced by Hcy in endothelial cells is regarded as the one of the mechanisms leading to these cardiovascular diseases. Previous studies have found that Hcy induces endothelial cells apoptosis mainly through the death receptor pathway, the mitochondrial apoptotic pathway and the endoplasmic reticulum stress pathway, but the exact mechanism for how Hcy induces apoptosis in endothelial cells is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited researches explaining the effects of Hcy on cancer cells [11] though numerous in vivo and in vitro studies have been performed to suggest its deleterious effects on normal cells [8,12,13]. It has been shown that Hcy accumulates in tumour sites because of dysfunction of methionine metabolism in cancer cells [14].…”
Section: Introductionmentioning
confidence: 99%